2020
DOI: 10.3390/ijerph17165941
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival in Women with High-Risk Endometrial Cancer and Comparisons of Sandwich versus Concurrent Adjuvant Chemotherapy and Radiotherapy

Abstract: Background: to elucidate the predictors of progression-free survival (PFS) and overall survival (OS) in high-risk endometrial cancer patients. Methods: the medical records of all consecutivewomen with high-risk endometrial cancer were reviewed. Results: among 92 high-risk endometrial cancer patients, 30 women experienced recurrence, and 21 women died. The 5-year PFS and OS probabilities were 65.3% and 75.9%, respectively. Multivariable Cox regression revealed that body mass index (hazard ratio (HR) = 1.11), pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
5
2
Order By: Relevance
“…In this study, we found the presence of para-aortic lymph node metastasis as the sole independent predictor of RFS in the multivariable analysis (Table 3), compatible with the study result of a retrospective study by Chen et al (hazard ratio = 11.11, p < 0.001) [14]. Similarly, lymph node status is considered to be the most important predictor for cancer outcome in a review article by Pijnenborg et al [15].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found the presence of para-aortic lymph node metastasis as the sole independent predictor of RFS in the multivariable analysis (Table 3), compatible with the study result of a retrospective study by Chen et al (hazard ratio = 11.11, p < 0.001) [14]. Similarly, lymph node status is considered to be the most important predictor for cancer outcome in a review article by Pijnenborg et al [15].…”
Section: Discussionsupporting
confidence: 88%
“…Since UPSC is a rare category of endometrial cancer, the patients with poor prognosis and have been diagnosed at an advanced stage. Studies have explored the survival characteristics of advanced stage endometrial cancer (Goodman et al, 2019, Chen et al, 2020. Solmaz et al (2016) found that LVSI was a significant covariate for the survival of endometrial cancer patients with UPSC but in our study we found it is not statistically significant.…”
Section: Discussioncontrasting
confidence: 78%
“…All‐cause mortality was the most frequently reported outcome ( n = 31), followed by recurrence ( n = 20) and endometrial cancer‐specific mortality ( n = 19; Table 1). Elevated BMI was associated with increased all‐cause mortality, endometrial cancer‐specific mortality, and cancer recurrence in 12, 15–17,21,26,48,51–53,64,67,69 2, 51,59 and 2 52,69 studies, respectively. One study noted a negative relationship between BMI and endometrial cancer‐specific mortality 55 .…”
Section: Resultsmentioning
confidence: 95%
“…Most of studies were conducted in Europe ( n = 20) 12,13,15,18,21,22,27,43–55 and North America ( n = 18) 19,20,23–26,56–67 . The remaining studies were conducted in Asia ( n = 4), 14,68–70 Oceania ( n = 2), 17,71 and South America ( n = 1) 72 . Only Martra et al 16 included participants from more than one location (USA and Italy).…”
Section: Resultsmentioning
confidence: 99%